THE INTENTIONAL SALES MANAGER - McManamon, Pat (Ascent Audio, 2020)
Until you harness the power of your own purposeful intention as a sales leader, your people will never deliver on their full potential. The Intentional Sales Manager shows how to launch, and sustain, the all-important process of personal and organizational transformation that drives the most successful sales teams.